Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2023
DOI: 10.1111/trf.17212
|View full text |Cite
|
Sign up to set email alerts
|

Survival in adult patients with chronic primary and secondary immune thrombocytopenia: A population‐based study

Abstract: Background Few studies have investigated long‐term survival in patients with primary immune thrombocytopenia (pITP). Further, changes in prognosis over the past decades and prognosis of secondary immune thrombocytopenia (sITP) are largely unstudied. Our objectives were to study comorbidity‐adjusted prognostic changes and causes of death in chronic pITP and sITP patients. Study Design/Methods Using nationwide Danish health registries 1980–2016, we identified 1762 patients with chronic pITP (median age 58 (IQR, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 49 publications
(130 reference statements)
0
11
0
1
Order By: Relevance
“…Despite therapeutic advances, life expectancy of patients with chronic ITP is still significantly reduced [25]. The chief causes are major hemorrhage including CNS bleeding, and infections associated with splenectomy or due to immunosuppressive therapy.…”
Section: Morbidity and Mortalitymentioning
confidence: 99%
“…Despite therapeutic advances, life expectancy of patients with chronic ITP is still significantly reduced [25]. The chief causes are major hemorrhage including CNS bleeding, and infections associated with splenectomy or due to immunosuppressive therapy.…”
Section: Morbidity and Mortalitymentioning
confidence: 99%
“…This is of interest as Denmark, as most of the western world, has an ageing population, with over 60 years of age being the fastest-growing sector of the population. 15 Prevalence does not plateau as neither incidence, as shown here, nor duration of disease 12 are fixed. Longer life expectancy for ITP patients contributing to increased prevalence may be attributed to improvement in treatment and/or earlier recognition, although further investigation is necessary to determine these relationships.…”
Section: Time Trends In Incidence and Prevalence Of Immune Thrombocyt...mentioning
confidence: 75%
“…In a recent study we showed that survival in cITP is improving, 12 and alongside an ageing population, longer duration of disease and previous trends point towards increasing incidence and prevalence. Hence a contemporary update of frequency measures for adult ITP is necessary.…”
Section: Time Trends In Incidence and Prevalence Of Immune Thrombocyt...mentioning
confidence: 92%
See 1 more Smart Citation
“…Die Lebenserwartung von Patient*innen mit chronischer ITP ist trotz aller therapeutischer Fortschritte immer noch deutlich reduziert [25]. Schwere Blutungen, inclusive ZNS-Blutungen, und Infektionen durch die immunsuppressive Therapie oder nach Splenektomie sind dafür verantwortlich.…”
Section: Mortalität Und Morbiditätunclassified